Implementasi Game Kahoot untuk Evaluasi Hasil Belajar Siswa - Cahyaningrum, Elief Fitriana (Lembaga Yasin AlSys, 2024)
The involvement of technology in the learning process is something that can facilitate the learning process so that learning becomes more effective and efficient. The method used is qualitative and the collection of data and information is using the literature study method. The purpose of this research is to describe the feasibility and effectiveness of game-based learning applications, namely the kahoot! In the learning process so that it can make it easier for teachers to evaluate the level of understanding of students in understanding the material that has been delivered within a certain period of time. With the kahoot! application, it is expected to foster students' motivation in learning so that it will foster a healthy spirit of competition and students can be encouraged to improve the quality of learning. The kahoot app is also able to create a fun learning atmosphere so that students can do quizzes with enjoyment and feel a new atmosphere while learning. The Kahoot app can also be used for free. So it can be concluded that the Kahoot! application developed by researchers is relevant and interesting to be used as a medium for evaluating student learning outcomes.